1980
DOI: 10.1111/j.1399-3054.1980.tb03299.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of artificial frost hardening and winter stress on net photosynthesis, photosynthetic electron transport and RuBP carboxylase activity in seedlings of Pinus silvestris

Abstract: Net photosynthesis of seedlings of Pinus silvestris has been measured and compared with the activities of photosynthetic electron transport and extracted RuBP carboxylase. The effects of prolonged frost hardening (photoperiod 8 h, + 3°C) followed by winter stress at subzero temperatures were analysed. There was a parallel effect of frost hardening and winter stress on the photosynthetic properties of both intact seedlings and isolated chloroplast thylakoids. The activity of extracted RuBP carboxylase was less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
3
2

Year Published

1981
1981
2001
2001

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 12 publications
(12 reference statements)
3
25
3
2
Order By: Relevance
“…In this study, the gas exchange reaction for needles of all stands and for the entire tree crowns was described using a shade leaf parameterization determined appropriate for the Fichtelgebirge region with high LAI (table III). The physiological capacity of Norway spruce needles for electron transport, carboxylation, and dark respiration varies seasonally in agreement with gas exchange observations from several other tree species [10,12,47,49]. We assumed that reduced soil water availability did not affect stomatal conductance during the summers 1994 and 1995 due to frequent rain events.…”
Section: Physiological Parameterizationsupporting
confidence: 66%
“…In this study, the gas exchange reaction for needles of all stands and for the entire tree crowns was described using a shade leaf parameterization determined appropriate for the Fichtelgebirge region with high LAI (table III). The physiological capacity of Norway spruce needles for electron transport, carboxylation, and dark respiration varies seasonally in agreement with gas exchange observations from several other tree species [10,12,47,49]. We assumed that reduced soil water availability did not affect stomatal conductance during the summers 1994 and 1995 due to frequent rain events.…”
Section: Physiological Parameterizationsupporting
confidence: 66%
“…The observed reduction in Fv / Fm noted in this study was not, however, accompanied by a change in shoot water status. Other studies have also shown a reduction in Fv / Fm during the coldest winter period that are thought to indicate winter photosynthetic "inactivation" [20], with reduced light-saturated rates of net photosynthesis and electron transport [30,31]. Despite the mild field temperatures experienced by seedlings in this study, declines, particularly in Φ PSII, were still evident indicating that either the plants are susceptible to relatively small temperature changes or other environmental factors are involved.…”
Section: Discussioncontrasting
confidence: 41%
“…The correlation between the PSII activity and the unsaturation level was less clear (r = 0.60; data not shown). We know from earlier studies (11,12,18,19) that the winter inhibition of overall electron transport occurs at the site of plastoquinone, which links the two photosystems. The plastoquinone content ofthe thylakoids also reaches a minimum level when this inhibition is most severe (12).…”
Section: Discussionmentioning
confidence: 99%
“…photosynthesis (22). Studies of pine seedlings exposed to artificial frosthardening (photoperiod, 8 h; 3°C) followed by winter stress in light at sub-zero temperature (photoperiod, 8 h; -5°C) showed that the decay and final winter inhibition of net photosynthesis was paralleled with an inhibition of the photosynthetic electron transport, whereas the activity of extracted ribulose-1,5-bisphosphate carboxylase was much less inhibited (18). It has also been shown (1 1, 13, 19) that the primary site of winter-induced inhibition of electron transport in pine is at the site of plastoquinone, although the capacities of the partial reactions of the two photosystems also decayed during prolonged winter stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation